VD_FINDINFO 38/2015 vom 7. Dezember 2015 - VD Tribunal cantonal (2015)
RÉCUSATION, PRÉSIDENT, TRIBUNAL DES PRUD'HOMMES, ADMISSION DE LA DEMANDE | 6 ROTC, 47 al. 1 let. f CPC (CH), 48 CPC (CH), 8a al. 3 CDPJ, 8b al. 4 CDPJ